Global issues and ethical considerations in human enhancement technologies - Thompson, Steven John, 1956- (Medical Information Science Reference, and imprint of IGI global, 2014)
"This book compiles prestigious research and provides a well-rounded composite of role of human enhancement technologies in emerging areas for those involved in computer science and the humanities, as well as many engaged in a humanities approach to metasystems, new artificial life, and robotics"-- Provided by publisher.
Keywords: Biomedical engineering -- Research -- Moral and ethical aspects.; Human experimentation in medicine -- Moral and ethical aspects.; Medical instruments and apparatus.; Biomedical engineering.; Biomedical Enhancement -- ethics; Equipment and Supplies; Génie biomédical -- Recherche -- Aspect moral.; Expérimentation humaine en médecine -- Aspect moral.; Médecine -- Appareils et instruments.; Génie biomédical.; biomedical engineering.; HEALTH & FITNESS -- Holism.; HEALTH & FITNESS -- Reference.; MEDICAL -- Alternative Medicine.; MEDICAL -- Atlases.; MEDICAL -- Essays.; MEDICAL -- Family & General Practice.; MEDICAL -- Holistic Medicine.; MEDICAL -- Osteopathy.; Human experimentation in medicine -- Moral and ethical aspects; Medical instruments and apparatus; Digital society; Emerging technologies; Engineering ethics; Freedom in experimentation; Human enhancement technology; Human rights and values; Human-computer interface